2015
DOI: 10.1111/cdev.12365
|View full text |Cite
|
Sign up to set email alerts
|

Late Emergence of the First Possession Heuristic: Evidence From a Small‐Scale Culture

Abstract: Western preschool children often assign ownership based on first possession and some theorists have proposed that this judgment might be an early emerging, innate bias. Five- to 9-year-olds (n = 112) from a small-scale group in Kenya (Kikuyu) watched videotaped interactions of two women passing an object. The object's starting position and the women's gestures were varied. Use of the first possession heuristic increased with age, and 8- to 9-year-olds performed similarly to German 5-year-olds (n = 24). Startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Our finding that even preschool children are sensitive to privacy concerns may reflect the focus on autonomy and independence in the United States, which differs from that of more collectivist or interdependent societies (Markus & Kitayama, ). It would be valuable to gather comparative data from cultural contexts that differ in this regard (see Kanngiesser, Rossano, & Tomasello, ). Another unresolved issue concerns the role of prior experience with technology.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that even preschool children are sensitive to privacy concerns may reflect the focus on autonomy and independence in the United States, which differs from that of more collectivist or interdependent societies (Markus & Kitayama, ). It would be valuable to gather comparative data from cultural contexts that differ in this regard (see Kanngiesser, Rossano, & Tomasello, ). Another unresolved issue concerns the role of prior experience with technology.…”
Section: Discussionmentioning
confidence: 99%
“…It would be informative to test if preferences for original objects are less pronounced or even absent in cultures where attachment objects are less typical. Relatedly, multiple studies have found cultural variation in children's reasoning about ownership and owned objects (e.g., Kanngiesser, Rossano, & Tomasello, 2015; Rochat et al, 2014). These differences suggest a fruitful arena for addressing how cultural practices may influence children's object concepts and value.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that the principle of first possession is central to both children's [5,9,10] and adults' [11] reasoning about ownership. Developmental researchers have shown that the notion that possession produces ownership is already present in young children and stays with us throughout our adult life.…”
Section: First Possession In Legal Cultural and Psychologicalmentioning
confidence: 99%
“…Previous research has demonstrated the relevance of the first possessor heuristic both in children and in adults [9,10]. However, it is easy to create a narrative that does not elicit the application of the first possession principle.…”
Section: Importance Of the First Possession Principle In Children Andmentioning
confidence: 99%